What Works in Conservation 2020 - Sutherland, William J.; Dicks, Lynn V.; Petrovan, Silviu O.; Smith, Rebecca K. (What Works in Conservation Serie, 2020)
" Is reduced tillage in arable fields beneficial for farmland biodiversity? Is prescribed burning in grasslands beneficial for bird conservation? Does livestock exclusion from degraded peatlands benefit peatland conservation? Is the provision of artificial shelters effective for subtidal benthic invertebrate conservation? Do wind turbine modifications reduce bat fatalities? Does adding topsoil increase the abundance of heathland plants? Are interventions to reduce road impacts on amphibians effective? Do herbicides control invasive parrot's feather? What Works in Conservation has been created to provide practitioners with answers to these and many other questions about practical conservation. This book provides an assessment of the effectiveness of conservation interventions based on summarized scientific evidence. The 2020 edition contains new material on mammals, birds, marine benthic invertebrates, bat conservation and wetlands. Other chapters cover practical global conservation of primates, peatlands, shrublands and heathlands, management of captive animals as well as an extended chapter on control of freshwater invasive species, the global conservation of amphibians, bats, birds and forests, conservation of European farmland biodiversity and some aspects of enhancing natural pest control, enhancing soil fertility and control of freshwater invasive species. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually, and provides full references. This is the fifth edition of What Works in Conservation, which is revised on an annual basis. Arcadia, DEFRA, ESRC, MAVA Foundation, NERC, Natural England, Robert Bosch Stiftung, Synchronicity Earth, South West Water and Waitrose Ltd. have generously contributed towards the publication of this volume."